Resilience, optimism, and burnout in high-performance youth athletes - Trujillo Santana, T.; López-Morales, J.L.; Romero, J.; Peinado Portero, A. I.; Zepeda Munguia, H.; Garcés De Los Fayos, E. J. (International Journal of Sport Psychology, 2023)
Background High-performance sport`s main goal is for athletes to perform at their maximum level in order to attain maximum possible success. Enhancing performance is one of the most studied areas in sport and performance psychology, with resilience being one of the most prominent variables in these studies.